2002
DOI: 10.1006/nimg.2002.1084
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Individual Target Brain in the Talairach Coordinate System

Abstract: The goal of regional spatial normalization is to remove anatomical differences between individual three-dimensional brain images by warping them to match features of a single target brain. Current target brains are either an average, suitable for low-resolution brain mapping studies, or a single brain. While a single high-resolution target brain is desirable to match anatomical detail, it can lead to bias in anatomical studies. An optimization method to reduce the individual anatomical bias of the ICBM high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 27 publications
(37 reference statements)
0
90
0
Order By: Relevance
“…Of course, there should be no expectation that the two approaches, which also employ different warping methods (piecewise-linear versus non-linear), should produce identical results. Templates based on averaging multiple brains (e.g., Tal50, MNI305, IA38) should incorporate fewer spatial biases than the classic, single-brain based Tal transformation (Kochunov et al, 2002). We found that while the different transformations provide similar results, there were many instances in which the templates provided somewhat divergent patterns of transformation from the native space.…”
Section: Comparing Transformation Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Of course, there should be no expectation that the two approaches, which also employ different warping methods (piecewise-linear versus non-linear), should produce identical results. Templates based on averaging multiple brains (e.g., Tal50, MNI305, IA38) should incorporate fewer spatial biases than the classic, single-brain based Tal transformation (Kochunov et al, 2002). We found that while the different transformations provide similar results, there were many instances in which the templates provided somewhat divergent patterns of transformation from the native space.…”
Section: Comparing Transformation Methodsmentioning
confidence: 82%
“…Spatial transformation is also an essential component of tissue-density-based statistical techniques, such as voxelbased morphometry (Ashburner and Friston, 2000) and other tissue-based assessment tools (Mega et al, 2005). Lastly, group-level functional neuroimaging analyses rely on spatial normalization (Fox et al, 1985;Mazziota et al, 2000;Kochunov et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A conservative threshold for statistical significance was set at po0.05 (false discovery rate corrected) with a minimum cluster size of 400 mm 3 . We used MRIcron software (http:// www.sph.sc.edu/comd/rorden/mricron/) to visualize ALE maps overlaid onto a high-resolution brain template generated by the International Consortium for Brain Mapping (Kochunov et al, 2002).…”
Section: Ale Meta-analysesmentioning
confidence: 99%
“…Three different ALE maps were computed for all Stroop studies, Stroop studies that required an overt or covert verbal response, and Stroop studies that required a manual response. Whole-brain maps of the ALE values were imported into AFNI [Cox, 1996] and overlaid onto an anatomical template generated by spatially normalizing the International Consortium for Brain Mapping (ICBM) template to Talairach space [Kochunov et al, 2002].…”
Section: Activation Likelihood Estimationmentioning
confidence: 99%